New certificateless aggregate signature scheme with universal designated verifier - Zhi-yan XU; Li-bing WU; Li LI; De-biao HE (Tongxin xuebao)
Certificateless aggregate signature(CLAS) schemes with universal designated verifier had been widely applied in resource-constrained wireless mobile networks,because they could not only solve the problems of the certificate management and private key escrow,but also realize batch validation and the signer’s privacy protection.A security analysis for a certificateless aggregate signature scheme with universal designated verifier was firstly provided,and two attack methods to demonstrate that their scheme was forgeable was presented.To enhance security,a new certificateless aggregate signature scheme with universal designated verifier was proposed,and then the security of the scheme in the random oracle model was proved.The performance of our proposed scheme was finally evaluated.Compared with the original scheme,the pvoposed scheme fixes the security flaws and the total computational cost is greatly reduced.